Aboriginal Citizenship: Sections 35, 25 and 15 of Canada's Constitution Act, 1982 - Christie, Gordon (Citizenship Studies, 2003)
Citizenship is a key factor in the development of national identity. Any system for establishing and defining citizenship is meaningless as a tool for the creation of such an identity, however, without control of the mechanisms by which this system is designed and implemented. In this paper I propose to examine the constitutional status of an Aboriginal right to control the design and implementation of citizenship codes. As the judiciary in Canada begins to grapple with questions of Aboriginal self-determination, it must begin to consider the extent to which its own vision of Canada as a constitutional democracy, currently engaged in a project of reconciling Aboriginal peoples to the sovereignty of the Crown, will set out parameters for locating and constructing such a right. Within the confines of constitutional law in Canada, do Aboriginal peoples have a right to design and implement their own citizenship codes, free from interference from Canadian governments? Alternatively, is there such a right, but subject to some measure of control by the Crown, and perhaps subject to other constitutional instruments, such as the Charter of Rights and Freedoms?